INVESTIGATION AND USE OF THE LITHUANIAN FLAX GENETIC RESOURCES IN THE BREEDING PROGRAMS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
The profusion, diversity and value of genetic resources significantly contribute to the success of flax breeding. Of special value are genotypes of local origin, highly adapted to the local climatic and soil conditions. Storage of genetic resources in Lithuania was started in 1994-1995. During the period 1995-1997 25 flax varieties and local accessions were studied at the Upytė Research Station of LIA. In 1998-2000 we tested 21 varieties and breeding lines, in 2001-2002 18 accessions, in 2003-2004 12 accessions. The best genotypes were included in flax breeding programs. About 50 genotypes have been transferred to the Gene Bank of the Lithuanian Institute of Agriculture after assessment for biological-agronomical characters following UPOV descriptors.